THE EFFECTIVENESS OF THE FAMILY ASSISTANCE TEAM PROGRAM POLICY IN HELPING REDUCE STUNTING RATES IN THE GUNUNGGURUH DISTRICT, SUKABUMI REGENCY - Nur Intan Marienda; Erry Sunarya; Asep Hikmat (DIA: Jurnal Administrasi Publik, 2025)
The TPK consists of a group of personnel including Midwives, Family Welfare Program Cadres, and Family Planning Cadres to provide assistance such as counseling, referral services facilitation, and facilitating the acceptance of social assistance programs for prospective brides/couples of reproductive age, pregnant women, postpartum mothers, children aged 0-59 months, as well as conducting surveillance of families at risk of stunting to early detect stunting risk factors. However, in its implementation, there are several issues such as the insufficient number of healthcare personnel in each village team, the increasing cases of stunting in the Gunungguruh District, and the suboptimal performance of TPK. Based on these phenomena, the researchers are interested in analyzing the effectiveness of TPK implementation, especially in the Gunungguruh District, using qualitative descriptive methods. The researchers use Matland's theory, employing indicators such as policy appropriateness, implementation appropriateness, target appropriateness, environmental appropriateness, and process appropriateness. This study uses purposive sampling with 12 informants consisting of local government officials, district officials, village officials, and community members, employing data collection techniques including interviews, literature reviews, and observations. The analysis results according to Matland's theory lead to the conclusion that the TPK Program Policy implemented in the Gunungguruh District, Sukabumi Regency, generally has not been effective. Factors hindering the implementation of the TPK program include budget constraints, lack of community awareness, minimal training implementation, and suboptimal coordination among relevant agencies. Efforts to improve the implementation of the TPK program include increasing the budget, raising community awareness, enhancing knowledge and training, and improving coordination among relevant agencies.